2008
DOI: 10.1002/ajmg.a.32361
|View full text |Cite
|
Sign up to set email alerts
|

Aging in people with specific genetic syndromes: Rett syndrome

Abstract: The aging process of people with intellectual disabilities has been a topic of interest in recent years. Good knowledge of the specific healthcare problems in adults with intellectual disabilities and anticipating on these problems are important issues in providing support and healthcare for these persons. Nevertheless little is known about the aging process of people with specific syndromes, like Rett syndrome. In association with the Dutch Rett syndrome parent association, 70 postal questionnaires were sent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
54
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(65 citation statements)
references
References 34 publications
10
54
1
Order By: Relevance
“…These prevalence data are consistent with proportions reported by smaller sample size ( n  = 53 [26], n  = 143 [34], n  = 145 [35]) parent-report studies for breath-holding. Slightly higher prevalences of breath-holding (76.9%) and hyperventilation (58.2%) were reported in a smaller ( n  = 91) and slightly older (4–47 years, mean 20.5 years) Italian population [28].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These prevalence data are consistent with proportions reported by smaller sample size ( n  = 53 [26], n  = 143 [34], n  = 145 [35]) parent-report studies for breath-holding. Slightly higher prevalences of breath-holding (76.9%) and hyperventilation (58.2%) were reported in a smaller ( n  = 91) and slightly older (4–47 years, mean 20.5 years) Italian population [28].…”
Section: Discussionsupporting
confidence: 88%
“…Although progress continues to be made towards understanding the mechanisms underlying the abnormal respiratory patterns [8, 18, 2125], estimates of prevalence for these features have only been reported in relatively small samples ( n  < 150) and range widely between 58 and 94% for breath-holding [7, 1012, 2628] and 26 and 100% for hyperventilation [7, 1012, 2628]. Breath-holding and hyperventilation have been reported to occur in girls 7 years of age and younger ( n  = 47 [9], n  = 12 [29]).…”
Section: Introductionmentioning
confidence: 99%
“…24 Cross-sectional studies suggest that women with RTT are generally healthy, and may improve with respect to function and comorbidities during adolescence and adulthood. 25,26 Yet, few longitudinal studies have examined survival or risk factors for mortality in RTT. In a cohort of 53 Dutch adult women with RTT, only 37 were successfully followed for 5 years, and 7 died.…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, the data available on age-related changes in Rett syndrome were limited to those derived from the early Swedish work (Witt-Engerström, 1992) carried out in the period prior to any knowledge of the genetic basis of Rett syndrome and those based on our own, earlier, cross-sectional data (Colvin et al, 2003). However in the past couple of years two studies have specifically examined the disorder profile into adulthood of Rett syndrome in general and of particular genotypes (Halbach et al, 2008; Smeets, Chenault, Curfs, Schrander-Stumpel, & Frijns, 2009). The first, a questionnaire study on 53 adults identified the major morbidities as neurological, respiratory and behavioural (Halbach et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However in the past couple of years two studies have specifically examined the disorder profile into adulthood of Rett syndrome in general and of particular genotypes (Halbach et al, 2008; Smeets, Chenault, Curfs, Schrander-Stumpel, & Frijns, 2009). The first, a questionnaire study on 53 adults identified the major morbidities as neurological, respiratory and behavioural (Halbach et al, 2008). The second identified specifically milder disorder profiles for those with p.R133C, p.R306C and C-terminal deletions (Smeets et al, 2009).…”
Section: Discussionmentioning
confidence: 99%